Psychological Pressure in Changes of Food Preference Among Generation Z of Psychology Students of the Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researcher conducted this study to evaluate the psychological pressure on changes infood preference among Gen Z psychology students.The result showed the ages of twenty-one (21) to twenty-three (23) represent the highestfrequency of the respondent in total, at 45%. CIS-GENDER comprises the majority of thesample, with 78 respondents, while LGBTQAT comprises twenty-two (22) respondents. Thecomposite mean result of stress (2.43), depression (2.05), and the highest composite meanresult of anxiety (2.77) revealed that the majority of respondents believe that food can reduceanxiety. Next, the composite mean result for families (2.88) shows that respondents preferhomemade food. Meanwhile, friends (2.60) show that the respondent loves to eat fast foodwith friends.According to the study, there is currently psychological pressure on psychology students toalter their eating preferences. It is advised that individuals be more conscious of their foodpreferences and observant of their emotions. Their acquaintances ought to showconsideration as well.
Keywords: Social Sciences